Nursing of a patient with wound exposed to seawater complicated with allergic dermatitis (1例海水感染伤口合并过敏性皮炎患者的护理) - LIN Longzhu (林龙珠); XIN Shuai (辛帅); WANG Jianhua (王建华); ZHENG Yizhen (郑移真); CAI Hua (蔡骅) (中西医结合护理)
This paper summarized the nursing management of a case of traumatic wound complicated with allergic dermatitis caused by seawater exposure and seawater immersion. According to the patient's condition, the active factor biological dressings and functional dressings, anti-allergy combined treatment, supplemented by wound care and psychological care and other interventions, were applied to promote wound healing. (本文总结1例受海浪冲击和海水浸泡的创伤性伤口合并过敏性皮炎患者的护理经验。根据患者伤口情况, 在抗过敏治疗的基础上, 联合应用活性因子生物敷料和功能性敷料, 辅以伤口护理、皮炎护理、营养支持、心理护理等护理措施, 有效促进患者伤口愈合。)